Catalytic pyrolysis of chicken fat waste using zeolite catalysts for biodiesel production - Liew, Mei Yi (2014)
Chicken fats become a major poultry waste from broiler industries and the production rate is increasing with human population. The conversion of waste chicken fats containing major triglycerides into potential biodiesel was investigated under non-catalytic and catalytic pyrolysis process using ZSM-5, HY and FCC zeolite catalyts (0.2-1.0 wt. %). Pyrolysis was conducted using lab-scale distillation set-up upon the variation of temperature, reaction time and nitrogen flow rate from 325-425°C, 10-50 min and 100-500 ml/min, respectively, to study the effect on the production of tar, pyro-oil and gas. Based on the analysis, increase of temperature, reaction time and nitrogen flow rate caused an increase of pyro-oil and gas, and a decrease of tar. This phenomena happened as a result of efficient thermal decomposition of biomass with excessive retention time led to an increase to the production of pyrolyzed gas and formation of pyro-oil. The maximum yield of pyrooil (73.81%) occurred at temperature 425°C, 30 minutes under nitrogen flow rate of 300 ml/min producing tar and gas at 17.57% and 8.62%, respectively. From catalytic pyrolysis, 0.8% loading of ZSM-5 and FCC, and 0.6% loading of HY produced the maximum yield of pyro-oil at which FCC showed the greatest increment at 18.97%. Pyro-oils were further analysed by Gas Chromatography-Mass Spectroscopy (GCMS) and Fourier-Transform Infrared Spectroscopy (FTIR) in order to identify their chemical properties and functional groups. From the GCMS analysis, different short hydrocarbon chain products in the range of C4 – C31 were found with dominant by chemical class of aliphatic, followed by carboxylic acid, cycloaliphatic, aromatic, ketone, ester and anhydride. The GCMS results were supported by related functional groups determined by FTIR, which are O-H hydroxyl group stretch, C=O carbonyl group stretch, C-O stretch, C-H aliphatic stretch, -CH2- aliphatic stretch and C-H bending (out-of-plane). Zeolites showed their selectivity in the production of aliphatic, cycloaliphatic and aromatic. ZSM-5 displayed the greatest increment of aliphatic (16.06%) and aromatic (1.79%). Meanwhile, FCC showed the greatest influence in reducing carboxylic acid by 16.15%. The presence of catalysts also affected the physical properties with the decrease of density, viscosity, acid value, saponification value, flash point, cloud point and pour point, and the increase of calorific value. As compared to Brazilian diesel fuel specification and ASTM D6751 standard, pyro-oils adequately met the qualifications except their acid values were out of the range of limit. Additionally, catalytic pyro-oils found high in calorific value had showed its commercial value to use in supplying heat and electricity for vehicle engine, burner, broiler and stirring engine.